Work-based learning for the engineering field in vocational education: Understanding concepts, principles and best practices - Jalinus, Nizwardi; Syahril; Haq, Syaiful; Kassymova, Gulzhaina Kuralbayevna (Researcher and Lecturer Society, 2023)
Various learning models have been developed and implemented in vocational education in the engineering field, but still have weaknesses, especially in basic matters such as one-sided learning and lack of direct industrial involvement. Moreover, learning in educational institutions is not supported by facilities that match those in the industry, but only simulation tools. Additionally, the media used in educational institutions is not as sophisticated as that used in the industry. This study is a literature review on Work-based Learning (WBL) and the formulation of WBL concepts suitable for vocational education in the engineering field. The results of the literature review showed that the implementation of WBL in various developing and advanced countries is very effective in developing students' competencies. Educational institutions and industries work together to improve the quality of learning to produce job-ready graduates. Industries benefit from the availability of competent and professional workforce who can develop their business for global competition. There are three WBL model concepts that can be applied to vocational education in the engineering field, including integrated student work, teaching factory, and industrial internship. The formation of student competencies can be carried out through a structured program, where students will gain experience and opportunities to gradually sharpen their competencies.